2012
DOI: 10.1161/circulationaha.111.038125
|View full text |Cite|
|
Sign up to set email alerts
|

Gremlin Plays a Key Role in the Pathogenesis of Pulmonary Hypertension

Abstract: Background-Pulmonary hypertension occurs in chronic hypoxic lung diseases, significantly worsening morbidity and mortality. The important role of altered bone morphogenetic protein (BMP) signaling in pulmonary hypertension was first suspected after the identification of heterozygous BMP receptor mutations as the underlying defect in the rare heritable form of pulmonary arterial hypertension. Subsequently, it was demonstrated that BMP signaling was also reduced in common forms of pulmonary hypertension, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
107
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 44 publications
11
107
0
Order By: Relevance
“…51 Although its contribution to neovascularization and tumor growth in experimental and human neoplasms deserves further investigation, our data support the notion that gremlin produced by tumor cells may induce angiogenesis by interacting directly with ECs and by stimulating the recruitment of a proangiogenic inflammatory infiltrate. Accordingly, previous observations have shown that gremlin upregulation may play a pathogenic role in different chronic inflammatory conditions, including hypoxic pulmonary hypertension, 52 diabetic nephropathy, 53 and lung fibrosis. 54 Indeed, gremlin haplodeficiency reduces vascular remodeling in hypoxic lung and diabetes mellitus-associated kidney damage.…”
Section: Discussionmentioning
confidence: 97%
“…51 Although its contribution to neovascularization and tumor growth in experimental and human neoplasms deserves further investigation, our data support the notion that gremlin produced by tumor cells may induce angiogenesis by interacting directly with ECs and by stimulating the recruitment of a proangiogenic inflammatory infiltrate. Accordingly, previous observations have shown that gremlin upregulation may play a pathogenic role in different chronic inflammatory conditions, including hypoxic pulmonary hypertension, 52 diabetic nephropathy, 53 and lung fibrosis. 54 Indeed, gremlin haplodeficiency reduces vascular remodeling in hypoxic lung and diabetes mellitus-associated kidney damage.…”
Section: Discussionmentioning
confidence: 97%
“…The most common of these mechanisms works through the action of secreted extracellular antagonists that function to directly neutralize BMP ligands to inhibit signaling. The spatial and temporal interplay of BMP ligands with their secreted extracellular antagonists is critical to focus and fine-tune signaling for normal development and homeostasis, where misregulation of this balance causes or perpetuates innumerable different disease states, including osteoarthritis, several cancer phenotypes, diabetic kidney nephropathy, and pulmonary arterial hypertension (3,(5)(6)(7)(8)(9)(10)(11). Although BMP ligands are structurally similar, their extracellular antagonists are highly diverse, spanning large multidomain proteins, as seen for the Follistatin and Chordin families of antagonists, to small, single domain proteins, such as Noggin and members of the DAN family (1,3,4,12).…”
mentioning
confidence: 99%
“…Relevant to this finding, several groups have identified increased Gremlin1 levels in a range of cancers, including colon, pituitary, malignant mesothelioma, cervical and pancreas cancers [16,17]. Importantly, levels of Gremlin1 have been shown to be elevated in human biopsies from patients with DN [11], pulmonary arterial hypertension (PAH) [10], non-ischaemic heart failure [18] and liver fibrosis [19]. In this issue of J Mol Med, Staloch and colleagues have identified a new role for Gremlin1 as a novel biomarker and potential therapeutic target in CP [20].…”
mentioning
confidence: 91%
“…Gremlin1 is involved in physiological processes such as limb and digit formation and nephrogenesis [9]. Increased Gremlin1 expression has been identified in fibrosis associated with kidney, lung, heart and liver disease [10,11]. Targeting Gremlin1 by gene deletion or shRNA knockdown reduced the severity of kidney disease in mouse models of diabetic nephropathy (DN) [12,13].…”
mentioning
confidence: 99%